If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -39 + -3x = 65 + 5x Solving -39 + -3x = 65 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -39 + -3x + -5x = 65 + 5x + -5x Combine like terms: -3x + -5x = -8x -39 + -8x = 65 + 5x + -5x Combine like terms: 5x + -5x = 0 -39 + -8x = 65 + 0 -39 + -8x = 65 Add '39' to each side of the equation. -39 + 39 + -8x = 65 + 39 Combine like terms: -39 + 39 = 0 0 + -8x = 65 + 39 -8x = 65 + 39 Combine like terms: 65 + 39 = 104 -8x = 104 Divide each side by '-8'. x = -13 Simplifying x = -13
| 8a-2c=-2 | | 0=-4x^2+9x+5 | | 1/2x+7=10.75 | | 4(x+4)+14=-2x | | 0.5x^2-3x=0 | | -9x+27=9y | | 10+10=100x | | (0-1)3x-y=1 | | 4a+7b=10 | | 0=4x^2+9x+5 | | 9+6=24x | | 5+4=8x | | 11=2+3y | | (8+w)(3w-4)=0 | | -3q=91.5 | | 3q=91.5 | | x-63=-9x+7 | | -14.1p+18.33=-16.12-19.4p | | 0=-8x^2+7x+6 | | x^3-19x^2+90x=56 | | -4/5m=5/7 | | x^3-19x^2+90x-56=0 | | 3(3.99)+1(x)=5x-.11 | | 5r-9=4 | | -14.08-2.4r=-1.2r-3.95-1.85 | | -20t=80 | | 2u+3+4u-18=114 | | x-62=57-6x | | -3(5x-2)=16x-5 | | 148+128+2x+(2x+40)=540 | | x-60=-10x+6 | | 132+x=22 |